Unconventional animal models for traumatic brain injury and chronic traumatic encephalopathy. Issue 10 (13th July 2021) - Ackermans, Nicole L.; Varghese, Merina; Wicinski, Bridget; Torres, Joshua; De Gasperi, Rita; Pryor, Dylan; Elder, Gregory A.; Gama Sosa, Miguel A.; Reidenberg, Joy S.; Williams, Terrie M.; Hof, Patrick R.
Abstract: Traumatic brain injury (TBI) is one of the main causes of death worldwide. It is a complex injury that influences cellular physiology, causes neuronal cell death, and affects molecular pathways in the brain. This in turn can result in sensory, motor, and behavioral alterations that deeply impact the quality of life. Repetitive mild TBI can progress into chronic traumatic encephalopathy (CTE), a neurodegenerative condition linked to severe behavioral changes. While current animal models of TBI and CTE such as rodents, are useful to explore affected pathways, clinical findings therein have rarely translated into clinical applications, possibly because of the many morphofunctional differences between the model animals and humans. It is therefore important to complement these studies with alternative animal models that may better replicate the individuality of human TBI. Comparative studies in animals with naturally evolved brain protection such as bighorn sheep, woodpeckers, and whales, may provide preventive applications in humans. The advantages of an in‐depth study of these unconventional animals are threefold. First, to increase knowledge of the often‐understudied species in question; second, to improve common animal models based on the study of their extreme counterparts; and finally, to tap into a source of biological inspiration for comparative studies and translational applications in humans.